2022
DOI: 10.1109/tvt.2022.3180748
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control for Unmanned Systems With One-Way Broadcast Communication

Abstract: Unmanned systems (USs) including unmanned aerial vehicles, unmanned underwater vehicles, and unmanned ground vehicles have great application prospects in military and civil fields, among which the process of finding feasible and optimal paths for the agents in USs is a kernel problem. Traditional path finding algorithms are hard to adequately obtain optimal paths in real-time under fast time-varying and poor communication environments. We propose an online optimal control algorithm for USs based on a one-way b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…To enhance the collaboration capability among robot clusters, Ge and Chen proposed a one‐way broadcast communication framework in which the robots can obtain the optimal path after receiving a message through the approximation theory of neural networks and gradient optimization techniques, whose shortcomings are the large bandwidth consumption and long communication delay during communication. [ 31 ]…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the collaboration capability among robot clusters, Ge and Chen proposed a one‐way broadcast communication framework in which the robots can obtain the optimal path after receiving a message through the approximation theory of neural networks and gradient optimization techniques, whose shortcomings are the large bandwidth consumption and long communication delay during communication. [ 31 ]…”
Section: Related Workmentioning
confidence: 99%
“…To enhance the collaboration capability among robot clusters, Ge and Chen proposed a one-way broadcast communication framework in which the robots can obtain the optimal path after receiving a message through the approximation theory of neural networks and gradient optimization techniques, whose shortcomings are the large bandwidth consumption and long communication delay during communication. [31] Many studies in recent years have shown that learning-based approaches are fruitful in decentralized control strategies for robots. [32] Most methods combine deep learning or reinforcement learning to achieve path finding with good generalization and high solution quality.…”
Section: Decentralized Approachmentioning
confidence: 99%